Do Job Coach Effective to PWDs Secured a Job in Malaysia - NOOR FATIHAH MAT RADZI (STIM LASHARAN JAYA MAKASSAR, 2020)
The right to work has been recognized through artice 23(1) of the Universal Declaration of Human Right 1948. But, opportunity and participation of Person With Disabilities (PWDs) in the workforce is still a challenge in Malaysian context. Various efforts and initiatives have been continuously undertaken to secure inclusion of PWDs in the workforce. Malaysia introduced Supported Employment (SE) through Job Coach programme largely provided by the Department of Social Welfare and other Non-Govermental Organizations (NGOs) focuses on helping PWDs in securing employment in the workplace. This conceptual paper discuss about the effectiveness Job Coach to PWDs enhancing participation in the open job market. Implications of the study to the organisation in particular and to the general public at large are also examined and to be considered in order to ensure PWDs inclusion in the workplace and their well-being could be continuously and effectively promoted.